The link between drug dependency and criminality: a systematic review - N.K. Tharshini,; Fauziah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Drug dependency is a complex and challenging condition that is strongly associated with increased criminal activity. The present review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines summarized the link between drug dependency and criminality. Keywords such as “drug dependency,” “criminality,” “drug-related offenses,” “psychoactive drugs,” “model of addiction,” “illicit drug,” “drug abuse,” and “crime” were typed into the Sage, Wiley Online Library, and PubMed databases to find information related to the link between drug dependency and criminality. The search covered open-access published articles from January 2018 to August 2022. The results indicate that a high proportion of drug-user crimes involve offenses such as crime against persons (e.g., murder, rape, and assault), property, and drug-related offenses. In light of these findings, greater consideration should be given to drug dependency, as it is a significant risk factor for criminal behaviour. Furthermore, the search results produced the identification of how different types of drugs may give rise to different patterns of criminal offending. Through this review, it is apparent that individuals with poly-drug consumption have a higher likelihood of engaging in diverse offense types. Thus, the key indicators of drug use and criminality should be explored in greater detail, particularly when the offense is disaggregated by types of crime. Moreover, there is a need to improve our understanding of the association between distinct drug-use types and various crime categories to circumvent naïve assumptions about drug-using offenders.